Analysis of stress-induced mobility enhancement on (100)-oriented single- and double-gate n-MOSFETs using silicon-thickness-dependent deformation potential. (20th March 2015) - Choi, Sujin; Sun, Wookyung; Shin, Hyungsoon
Abstract: The stress effect in uniaxially strained single- and double-gate silicon-on-insulator n -type metal oxide-semiconductor field effect transistors (MOSFETs) with a (100) wafer orientation is analyzed. A model of silicon-thickness-dependent deformation potential is introduced to accurately calculate the mobility using a Schrödinger–Poisson solver. Simulation results using the model exhibit excellent agreement with the measured mobility for both the unstrained and strained conditions. Electron mobility enhancements with longitudinal and transverse tensile stress conditions are simulated as a function of silicon thickness. The mobility enhancement in the single-gate case has one peak point, whereas it produces two peak points in the double-gate case. An in-depth analysis reveals that this phenomenon results from the hump in the energy difference between the Δ 2 and Δ 4 valleys, which in turn results from the volume inversion in the double gate.